Study Of Thin Films Of Isolated And Interacting Conducting Polymers - Lim, Thong Leng (2007)
Although organic display and other polymer related products can already be found in Volkswagon, the physics related to their photoluminescence and the underlying charge transportation are still not fully understood. It is the purpose of this theis to study the photoluminescence and charge transportation of conjugated polymers.